Prospects Challenges and Sustainability of the Agri-Food Supply Chain in the New Global Economy II - Skalkos, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The agri-food supply chain (AFSC) is undoubtedly a chain that must be transformed to adjust to the needs and requirements of the new era, following the COVID-19 pandemic. New challenges and prospects and the sustainability of the AFSC are already emerging, with the scientific community obliged to come up with answers and solutions to global food consumption issues. Scientific research concerning different aspects of the AFSC with selected topics, including technologies, new foods, consumers' perceptions, socioeconomic and environmental issues of conservation and sustainability, eco-innovation solutions, and green transformative pathways in the agri-food sector are included in this Special Issue. Emphasis is placed on the end users-the consumers-who need healthy, sustainable, value-added, economic food produced within the new global environmental, political, and social conditions which are currently, and for a long time have been, under a major transformation. The papers included in this Special Issue give practical, innovative, and sustainable solutions to existing drawbacks of the supply chain, thus providing useful knowledge to readers or researchers interested in these specific subject matters. This is the second Special Issue of a series of Special Issues that we initiated a year ago as a follow-up to the changes and progress of the AFSC, and we will continue this, with more Special Issues on the way, highlighting more and more scientific achievements in selected subject areas of the chain to our respected global readers.